Archaeologioal Reconnaissance in Hamilton Inlet and Lake Melville, Labrador, 1968 - William Fitzhugh (1969)
The initial field season of a planned two-year study of the archaeology of the central coast of Labrador has been completed. Aided by air-photo interpretation a survey of the transitional zone from the forested interior to the barren coast has resulted in recognition of a dual series of Indian and Eskimo components. At North West River small Indian sites spanning a period of about three thousand years have been excavated, and a five-stage sequence of occupation has been proposed. Surveys in Groswater Bay (Hamilton Inlet) suggest amplification of the NWR data to include an older unit using ground slate tools and late prehistoric unit which may represent prehistoric Naskaupi. Eskimo remains include recent historic sites within eastern Lake Melville, and a fine sequence of 16th-18th Century winter sites in the Narrows. Labrador Thule culture was not found but probably exists in the outer reaches of Groswater Bay. Finally, a series of small Dorset campsites was found on Ticoralak Island, indicating a regional variant of this culture with several new Dorset types represented. Very little evidence was found suggesting contact between Eskimo and Indian groups for any of this period. Dorset and Indian cultures contemporaneous with it are distinctly different in technology, typology, and geographic distribution. Other points to be discussed include a possible hiatus of Eskimo occupation between Dorset and Thule times, distributional evidence for several of the Indian components, and comments on cultural ecology and lithic analysis.